Reasons for late diagnosis of pulmonary echinococcosis in a non-endemic area - I. A. Krylova; S. N. Levitsky; I. A. Shabalina; A. V. Semenova; I. A. Turabov; И. А. Крылова; С. Н. Левицкий; И. А. Шабалина; А. В. Семёнова; И. А. Турабов (Translational Medicine, 2022)
Background. Diagnosis, treatment, prevention of echinococcosis remain relevant tasks for most Russian regions. One of the key problems is the diagnosis of this disease in non-endemic regions.Objective. To describe a clinical case of cystic echinococcosis of the lungs.Materials and methods. A multislice computed tomography of the chest with contrast enhancement, serological diagnosis and histological examination and subsequent surgical treatment of a 6-year-old patient were performed.Results. A case of cystic echinococcosis of the lungs in a 6-year-old boy is presented. Echinococcosis was diagnosed at the stage of a large diameter cyst during chest X-ray to exclude pneumonia. Surgical treatment was performed. The decrease in titers of antiparasitic antibodies in dynamics after the operation allowed to conclude that the patient had recovered. The presented clinical case demonstrates a typical error in the diagnosis of pulmonary echinococcosis. Cystic echinococcosis is a rare pathology in the Arkhangelsk region (up to 4 per year). This situation leads to late diagnosis of this helminthiasis. The main mistake in the diagnosis was the lack of alertness in relation to echinococcosis and, as a result, the establishment of an incorrect diagnosis — pneumonia.Conclusions. The use of multislice computed tomography of the chest with contrast enhancement, serological diagnosis and histological examination in combination allows you to accurately establish the diagnosis of echinococcosis of the lungs. Введение. Диагностика, лечение, профилактика эхинококкозов остаются актуальными задачами для большинства регионов России. Особую сложность вызывает диагностика данного заболевания в неэндемичных регионах.Цель. Описать клинический случай кистозного эхинококкоза легких.Материалы и методы. Была проведена многосрезовая компьютерная томография грудной клетки с контрастным усилением, серологическая диагностика, гистологическое исследование и последующее оперативное лечение пациента 6 лет.Результаты. Представлен случай кистозного ...